2005
DOI: 10.1109/lsp.2005.845606
|View full text |Cite
|
Sign up to set email alerts
|

A foundation for watermarking in compressed domain

Abstract: In this letter, we propose a fragile digital watermarking algorithm that is directly applicable to compressed bit streams and is mathematically lossless with practically no increase in file size. The algorithm exploits the inefficiency of the code space of popular compression standards by recognizing that not all code words appear in the bit stream. By mapping the code words to the outside of the used code space, we can embed the watermark into the stream as forced bit errors. The decoder recognizes such code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The approach in (Langelaar, 2000) is effective but is lossy, too predictable and requires Huffman decoding of the JPEG file, while (Fridrich, 2004) is an adaption of (Langelaar, 2000) to JPEG. A fragile but lossless and file preserving watermarking algorithm is proposed in (Mobasseri, 2005) that is applicable to any entropy coded compression stream, provided that the total code space is not used. Inter-block correlation of the selected DCT coefficients for JPEG compressed data, by adding or subtracting an off-set to the mean value of the neighboring DCT coefficients, are also used in (Choi, 2000) and in (Luo, 2002) to embed watermark.…”
Section: Related Work and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach in (Langelaar, 2000) is effective but is lossy, too predictable and requires Huffman decoding of the JPEG file, while (Fridrich, 2004) is an adaption of (Langelaar, 2000) to JPEG. A fragile but lossless and file preserving watermarking algorithm is proposed in (Mobasseri, 2005) that is applicable to any entropy coded compression stream, provided that the total code space is not used. Inter-block correlation of the selected DCT coefficients for JPEG compressed data, by adding or subtracting an off-set to the mean value of the neighboring DCT coefficients, are also used in (Choi, 2000) and in (Luo, 2002) to embed watermark.…”
Section: Related Work and Limitationsmentioning
confidence: 99%
“…On summarization of the review works, it is observed that watermark embedding in the bitstream domain (Mobasseri, 2005) is fragile and requires re-encoding at alternate bit rates. On the other hand, JWC works reported in (Wu, 2005) are mostly ad hoc and put primary focus on quantization (or compression) rate and embedding rate.…”
Section: Related Work and Limitationsmentioning
confidence: 99%
“…This new paradigm has been the subject of both deeply theoretical and application oriented investigations (see for instance [10] and [11]) and is still a very active research area (see [12] and [13]). Specific applications include attribution of medical images for clinical purposes, copyright protection of biological or satellite images, personal identification via fingerprinting or iris matching.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon explains that a nature JPEG picture could not use perfectly all VLC in the supplied codetable. According to the phenomenon in [2] [3], the idea is adopted that used VLC are mapped to unused ones in a JPEG picture. Watermark is embedded to the picture making use of the idea.…”
Section: Introductionmentioning
confidence: 99%